The harm principle, personal identity and identity-relative paternalism - Wilkinson, D (BMJ Publishing Group, 2023)
Is it ethical for doctors or courts to prevent patients from making choices that will cause significant harm to themselves in the future? According to an important liberal principle the only justification for infringing the liberty of an individual is to prevent harm to others; harm to the self does not suffice. In this paper, I explore Derek Parfit’s arguments that blur the sharp line between harm to self and others. I analyse cases of treatment refusal by capacitous patients and describe different forms of paternalism arising from a reductionist view of personal identity. I outline an Identity Relative Paternalistic Intervention Principle for determining when we should disallow refusal of treatment where the harm will be accrued by a future self, and consider objections including vagueness and non-identity. Identity relative paternalism does not always justify intervention to prevent harm to future selves. However, there is a stronger ethical case for doing so than is often recognised.